Potential gains: Comparison of a mono‐isocentric three‐dimensional conformal radiotherapy (3D‐CRT) planning technique to hybrid intensity‐modulated radiotherapy (hIMRT) to the whole breast and supraclavicular fossa (SCF) region. Issue 1 (6th May 2021) - Ambrose, Leigh; Stanton, Cameron; Lewis, Lorraine; Lamoury, Gillian; Morgia, Marita; Carroll, Susan; Bromley, Regina; Atyeo, John
Abstract: Introduction: Until late 2018, standard of practice at the Northern Sydney Cancer Centre (NSCC) for breast and nodal treatment was a conformal mono‐isocentric technique. A planning study comparing an existing mono‐isocentric three‐dimensional conformal radiotherapy (3D‐CRT) planning technique to a hybrid intensity‐modulated radiotherapy (hIMRT) approach for the whole breast and supraclavicular fossa (SCF) region was undertaken with the aim to improve plan quality by improving dose conformity/homogeneity across target volumes and reducing hotspots outside the target. Methods: A cohort of 17 patients was retrospectively planned using the proposed hIMRT technique, keeping the same planning constraints as the original treated breast and SCF 3D‐CRT plan and normalising the 3D‐CRT plans to achieve minimum breast/SCF target coverage to compare organs at risk (OARs). Normal tissue index (NTI) and homogeneity index (HI) were compared for plan quality as well as for evaluating OARs. Results: The hIMRT technique showed statistically significant improvements in NTI and HI, as well as improvement in maximum brachial plexus and thyroid doses. There was a negligible increase in maximum oesophagus dose which could be improved if used in optimisation. Other OAR doses in the irradiated region were comparable to the 3D‐CRT plans, however maximum doses were reduced overall. Conclusion: The hIMRT planning technique maintained clinically acceptable doses to OARs and reduced normal tissue dose while maintaining equivalent dose coverage to breast and SCF planning target volumes with improved conformity and homogeneity. The reduction in maximum doses promotes a favourable toxicity profile, with potential benefit of improved long‐term cosmesis. Abstract : The aim of this study was to design a plan that delivered a full intensity modulated radiotherapy (IMRT) technique to the breast and incorporated conformal and IMRT as a hybrid approach to the supraclavicular fossa (SCF) region to improve plan quality. The hybrid IMRT (hIMRT) technique maintained clinically acceptable doses to organs at risk (OARs) and reduced normal tissue dose while maintaining equivalent dose coverage to breast and SCF planning target volumes with improved conformity and homogeneity. The improved plan quality with the hIMRT technique has allowed us to deliver a minimum therapeutic dose to the SCF of 45 Gy in 25 fractions in this varied body habitus cohort whilst respecting OAR tolerances.